AC1MMYR2 impairs high dose paclitaxel-induced tumor metastasis by targeting miR-21/CDK5 axis. Issue 2 (1st July 2015) - Ren, Yu; Zhou, Xuan; Yang, Juan-Juan; Liu, Xia; Zhao, Xiao-hui; Wang, Qi-xue; Han, Lei; Song, Xin; Zhu, Zhi-yan; Tian, Wei-ping; Zhang, Lun; Mei, Mei; et al.
Abstract Paclitaxel (taxol) is a widely used chemo-drug for many solid tumors, while continual taxol treatment is revealed to stimulate tumor dissemination. We previously found that a small molecule inhibitor of miR-21, termed AC1MMYR2, had the potential to impair tumorigenesis and metastasis. The aim of this study was to investigate whether combining AC1MMYR2 with taxol could be explored as a means to limit tumor metastasis. Here we showed that abnormal activation of miR-21/CDK5 axis was associated with breast cancer lymph node metastasis, which was also contribute to high dose taxol-induced invasion and epithelial mesenchymal transition (EMT) in both breast cancer cell line MDA-MB-231 and glioblastoma cell line U87VIII. AC1MMYR2 attenuated CDK5 activity by functional targeting CDK5RAP1, CDK5 activator p39 and target p-FAKser732. A series of in vitro assays indicated that treatment of AC1MMYR2 combined with taxol suppressed tumor migration and invasion ability in both MDA-MB-231 and U87VIII cell. More importantly, combination therapy impaired high-dose taxol induced invadopodia, and EMT markers including β-catenin, E-cadherin and vimentin. Strikingly, a significant reduction of lung metastasis in mice was observed in the AC1MMYR2 plus taxol treatment. Taken together, our work demonstrated that AC1MMYR2 appeared to be a promising strategy in combating taxol induced cancer metastasis by targeting miR-21/CDK5 axis, which highlighted the potential for development of therapeutic modalities for better clinic taxol application.